The Use of Project Based Learning (PJBL) to Increase Students' Motivation and Understanding in Chemistry Learning at SMAN 1 Sreseh (Learning for Children with Special Needs) - Sefty Anggraeny; Soesiana Tri Ekawati Silver; Hetty Purnamasari (International Forum of Researchers and Lecturers, 2025)
This study examines the application of Project-Based Learning (PjBL) in chemistry learning at SMAN 1 Sreseh, with a focus on increasing motivation and understanding of concepts among students, especially Children with Special Needs (ABK: Anak Berkebutuhan Khusus). PjBL was chosen as an approach that can increase student engagement through the exploration of projects relevant to everyday life, allowing students to better understand abstract chemical concepts. The results showed that the application of PjBL could increase students' intrinsic and extrinsic motivation, with regular students experiencing a more significant improvement. Although ABK students show lower improvements, they also gain significant benefits in terms of understanding of chemistry concepts and active involvement in projects. This study confirms that PjBL is an effective learning method to increase motivation and understanding of concepts, especially for ABK students, in the context of inclusive education.